85.6k views
4 votes
Step by Step explanation of Vertex Form of f(x)=x^2-6x-40

User Tmp
by
5.6k points

1 Answer

2 votes

A quadratic in vertex form reads as

(x - a)² + b

where (a, b) is the vertex.

To get the given quadratic in this form, complete the square:

x² - 6x - 40 = x² - 6x + 9 - 49 = (x - 3)² - 49

Or, work backwards by expanding the vertex form and solving for a and b :

(x - a)² + b = x² - 2ax + a² + b

So if

x² - 6x - 40 = x² - 2ax + a² + b,

then

-2a = -6 → a = 3

a² + b = -40 → b = -49

User Jovian
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.